Analysis of Live Streaming Factors and Promotion on Purchase Decisions and Online Reviews as Mediating Variables on Tokopedia Play - Amarul Amarul; Yuda Supriatna; Sahabat Paulinus Johanna (International Forum of Researchers and Lecturers, 2025)
This study investigates the impact of live streaming, promotions, and online customer reviews on purchasing decisions among users of the Tokopedia platform in Indonesia. The rapid development of the internet, particularly during the COVID-19 pandemic, has transformed consumer behavior, leading to increased adoption of digital shopping methods. Utilizing a quantitative research design, data were collected from 130 respondents who have engaged with Tokopedia's live streaming feature, Tokopedia Play. The findings reveal that both live streaming and promotional strategies significantly influence online reviews and purchasing decisions, with coefficients of 0.426 and 0.445, respectively. Online reviews also play a critical mediating role, enhancing the relationship between live streaming, promotions, and purchasing decisions. The demographic analysis indicates that younger consumers, particularly those aged 17-26, dominate the user base, highlighting the need for tailored marketing strategies. Despite the positive outcomes, challenges such as the digital divide and cybersecurity concerns persist, necessitating strategic measures to enhance digital literacy and secure online transactions. The study concludes that leveraging live streaming, promotions, and positive online reviews can significantly enhance consumer engagement and drive sales in the competitive e-commerce landscape of Indonesia. Future research should explore the long-term effects of these variables on consumer loyalty and the impact of emerging technologies on the e-commerce experience.